Network youth communities in the social-cultural space of the northern region: methodological and empirical aspects of the study - L. A. Chizhova; A. G. Tutygin; R. S. Stirmanova (RUDN journal of Sociology)
Transformations in the contemporary society and social-cultural space have significantly changed social activity and decision-making based on retrospective attitudes, which is especially evident in the behavior of local groups of youth communities in the online space. In this study, the authors proceeded from the fact that local youth communities in northern regions (like Arkhangelsk) have unique territorial and mental features. The conducted analysis of environmental and musical (cultural) communities in the most popular social network in Russia “Vkontakte” allowed to identify a number of characteristics for the subsequent study of the conformal (threshold) behavior model. Thus, P. Jaccard’s community coefficients showed that the structural characteristics of the youth environmental online communities, partly filled with protest ideas, are not critical enough and have not reached threshold limits, i.e., there is no threat of protest transition from online to offline space. As a promising model for further studies of the youth online communities, the authors propose the game-theoretical approach as the most relevant for the empirical characteristics of online social networks. The proposed and illustrated approach can be applied in the study of the behavior of online communities of different thematic focus, with different age, gender, educational and other characteristics. In the future, the authors will verify models for assessing and predicting the behavior of local groups in social networks using the example of communities in northern regions and will provide a system of cases for decision-making in the interests of developing social-political and social attitudes of the youth.